Temperature-dependent properties of corroded super ductile TMT steel bars. (October 2021) - Tariq, Faraz; Bhargava, Pradeep
Highlights: Influence of various combinations of corrosion and elevated temperatures on the overall mechanical behaviour of SD TMT bars. Influence of corrosion in combination with exposure to elevated temperatures on ductility characteristics of SD TMT bars. Influence of corrosion in combination with exposure to elevated temperatures on strain hardening of SD TMT bars. Influence of corrosion in combination with exposure to elevated temperatures on ductile areas of SD TMT bars. Influence of corrosion in combination with exposure to elevated temperatures on the elongation ratio of SD TMT bars. Abstract: Super ductile TMT reinforcing steel bars are commonly used these days for RC constructions, given their excellent thermal properties. SD TMT rebars are superior due to their distinct cross-sectional phase distribution (CSPD) of martensite, bainite, and pearlite. This paper investigates the influence of the superimposition of corrosion-induced damage by the exposure to elevated temperatures on properties of reinforcing steel simulating corroded structural members exposed to an accidental fire. The experimental program involved exposing bare bars to accelerated corrosion to achieve desired corrosion levels in terms of mass loss using the impressed current accelerated corrosion technique to a precision level of ± 1%. Subsequently, the identical specimens were heated to 250 °C, 550 °C, 800 °C, and 950 °C and allowed to achieve a steady-state at that temperature before being cooled down to ambient temperatures in the furnace itself and tested in tension to failure. A detailed analysis of the effect of various combinations of corrosion-induced mass loss and elevated temperatures on ductility characteristics of reinforcing steel using various prevalent methods in the available literature is presented. The results indicate a notable reduction in reinforcing steel's critical mechanical properties due to the superimposition of the two phenomena.